Cellular senescence at the saphenofemoral junction in patients with healthy, primary varicose and recurrent varicose veins – A pilot study. (June 2022) - Mühlberger, Dominic; Zumholz, Anne-Katrin; Brenner, Erich; Mumme, Achim; Stücker, Markus; Falkenstein, Thomas; Hummel, Thomas
Objectives: Cellular senescence could play a role in the development of venous disease. Superficial venous reflux at the saphenofemoral junction is a common finding in patients with primary varicose veins. Furthermore, reflux in this essential area is associated with higher clinical stages of the disease and recurrent varicose veins. Therefore, this pilot study aimed to investigate cellular senescence in the immediate area of the saphenofemoral junction in patients with healthy veins, primary varicose veins and additionally in patients with recurrent varicose veins due to a left venous stump. Methods: We analyzed vein specimens of the great saphenous vein immediately at the saphenofemoral junction. Healthy veins were collected from patients who underwent arterial bypass reconstructions. Samples with superficial venous reflux derived from patients who received high ligation and stripping or redo-surgery at the groin, respectively. Sections were stained for p53, p21, and p16 as markers for cellular senescence and Ki67 as a proliferation marker. Results: A total of 30 samples were examined (10 healthy, 10 primary varicose, and 10 recurrent varicose veins). We detected 2.10% p53 + nuclei in the healthy vein group, 3.12% in the primary varicose vein group and 1.53% in the recurrent varicose vein group, respectively. These differences were statistically significant ( p  = 0.021). In the healthy vein group, we found 0.43% p16 + nuclei. In the primary varicose vein group, we found 0.34% p16 + nuclei, and in the recurrent varicose vein group, we found 0.74% p16 + nuclei. At the p  < 0.05 level, the three groups tended to be significant without reaching statistical significance ( p  = 0.085). There was no difference in respect of p21 and Ki67. Conclusion: We found significantly higher expression rates of p53 in primary varicose veins at the saphenofemoral junction than in healthy veins. p16 expression tended to be increased in the recurrent varicose vein group. These preliminary findings indicate that cellular senescence may have an impact in the development of varicose veins or recurrence. Further studies addressing this issue are necessary.